On some distributions involving general functions (1975)
In this note, two aspects in relation to distribution involving general functions are considered. Firstly, the distribution of the sum and also the ratio of two independent radom variables with densities including  ∅2 (a1,.... an; S; λ1 x, .. , λn x) and ψ2 (p ; b1 ..., bn ; t1 u .... tn y) is dealt with. The speciol case of n=2  is considered.  Also, the distribution oI the sum of variables with ∅2 and ∅3 as their densities is obtained. The second aspect is estimation. In ∅2 , a parameter is estimated and the estimate is put in the closed form in terms of the general function ψ2. Also, the Bayes estimate in the distribution involving the Bessel function Ip(cx) is obtained and is expressed in terms of another general function FA.